STRATEGI PENGEMBANGAN USAHA TERNAK AYAM PEDAGING (STUDI KASUS PADA USAHA PATRIOT DI DESA MASARI KECAMATAN PARIGI SELATAN KABUPATEN PARIGI MOUTONG PROVINSI SULAWESI TENGAH) - Tauhid, Moh.; Hadayani, Hadayani; Tangkesalu, Dance (AGROTEKBIS, 2019)
Broiler business in Patriot business still applies traditional farming system with such weaknesses as relatively simple production equipment, relatively high mortality rate and limited human resources. Data collected was analyzed using SWOT Analysis. The IFAS value was 3.22, with the strength value was 2.27 and the weakness value was 0.95. This shows that the strength factor in the